Avaliação da expectativa do consumidor: um exame empírico de duas propostas de operacionalização - Alexandre Inacio de Moura (2005)
In Natural Sciences, the concepts precise definitions are a vital step on theory development. At the same basis, some social scientists use the analogous argumentation to defend the idea that social constructs are only theoretically meaningful when they are precisely defined. Speaking of the Marketing discipline, the consumer expectation construct plays an important role on models that try to describe and explain consumerbehavior. However, according to Teas & Palan (1997), this construct fails to be theoretically meaningful since it holds multiple definitions on the literature. Trying to solve this problem, the authors had proposed the construct formalization. The present work operationalizes the consumer expectation construct on two ways: (1) from its nominal definition through natural language, proposed by Oliver (1980) and (2) from its nominal definition through formal language, proposed by Teas & Palan (1997).The results indicate that the formalization effort did not met the expected purpose, since the scale reliabilities were not statistically significant at the 0,05 level.